Wogonin, a natural flavonoid, intercalates with genomic DNA and exhibits protective effects in IL-1β stimulated osteoarthritis chondrocytes. (25th August 2017) - Khan, Nazir M.; Ahmad, Imran; Ansari, Mohammad Y.; Haqqi, Tariq M.
Abstract: Wogonin has recently been shown to possess anti-inflammatory and chondroprotective properties and is of considerable interest due to its broad pharmacological activities. The present study highlights that Wogonin binds DNA and exerts chondroprotective effects in vitro . Wogonin showed strong binding with chondrocytes genomic DNA in vitro . The mode of binding of Wogonin to genomic-DNA was assessed by competing Wogonin with EtBr or DAPI, known DNA intercalator and a minor groove binder, respectively. EtBr fluorescence reduced significantly with increase in Wogonin concentration suggesting possible DNA intercalation of Wogonin. Further, in silico molecular docking of Wogonin on mammalian DNA also indicated possible intercalation of Wogonin with DNA. The denaturation and FRET studies revealed that Wogonin prevents denaturation of DNA strands and provide stability to genomic DNA against a variety of chemical denaturants. The cellular uptake study showed that Wogonin enters osteoarthritis chondrocytes and was mainly localized in the nucleus. Wogonin treatment to OA chondrocytes protects the fragmentation of genomic DNA in response to IL-1β as evaluated by DNA ladder and TUNEL assay. Treatment of chondrocytes with Wogonin resulted in significant suppression of IL-1β-mediated induction of ROS. Further, Wogonin exhibited protective potential through potent suppression of extrinsic and intrinsic apoptotic pathways and induction of anti-apoptotic proteins in IL-1β-stimulated osteoarthritis chondrocytes. Our data thus suggest that DNA intercalation by Wogonin may result in the stabilization of genomic DNA leading to protective activity. Graphical abstract: Highlights: Wogonin exhibited intercalating ability with genomic DNA isolated from chondrocytes. Wogonin was found to be localized in the nucleus human osteoarthritis chondrocytes. Wogonin protected fragmentation of genomic DNA under pathological condition. Wogonin stabilized genomic DNA against chemical denaturants. Wogonin exhibited protective effect under osteoarthritis pathogenic condition.